Urinary prothrombin fragment 1 : a potential role-player in the protection of South African blacks from calcium oxalate kidney stone disease - Webber, Dawn (Department of Chemistry, 2016)
The incidence of kidney stones amongst South Africa's black population is rare. This is in contrast to the white population, whose stone rate is similar to that in Western society. Urine composition alone does not account for these differences. This thesis presents a study of the inhibitory role of the protein, urinary prothrombin fragment 1 (UPTFI ), and its biochemical characterisation in both population groups. In a preliminary study, the urine composition and inhibitory activity of urine and urinary macromolecules from healthy white and black subjects was compared using a spectrophotometric sedimentation assay, zeta potential measurements and particle size analysis. Results suggested greater inhibition by urinary macromolecules in the black group. UPTFI was isolated from calcium oxalate (CaOx) crystals and purified by reverse phase (RP)-high performance liquid chromatography (HPLC) from the urine of healthy white (WFl) and black (BFl) subjects. The identity of the purified proteins was confirmed by Western blotting, N-terminal protein sequencing, matrix-assisted laser desorption ionisation time-of-flight (MALDI-TOF) mass spectrometry (MS), amino acid analysis and 2D sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE); these analyses did not indicate differences in the protein backbone from the two groups. However, alkaline amino acid analysis showed the presence of more y-carboxyglutamic acid (Gla) residues in BFI. The N-and 0-linked glycans were released by enzymatic and chemical reactions, respectively, and sequenced using exoglycosidase digestions in tandem with RP and weak anion exchange HPLC, as well as MS. These analyses demonstrated a high proportion of sialylated glycans on UPTFl and a greater number of sialic acid residues on BFI. Molecular modeling located the glycans on the protein's kringle domain and identified a potential mode by which crystallisation could be inhibited.